The Relationship between the Improvement Level in Blood Gas Parameters in Time and Brain MRI Findings in Newborns with the Diagnosis of Hypoxic Ischemic Encephalopathy - Aslan Yilmaz; Abdulkerim Uygur; Barıs Celik; Ali Metin Akdag; Demet Baser; Sureyya Ipek Ozturk (Turkish Archives of Pediatrics)
Objective: In this study, we aimed to evaluate the relationship between the level of improvement in blood gas parameters in the first hours of age and normal and diffusion-restriction brain magnetic resonance imaging (MRI).